(untitled) (Perner’s Contacts, 2016)
The paper investigates heterogeneity of business travelers who travel with different types of air carriers. According to a set of studies published abroad it is researched that there are business passengers traveling with full-service carriers or with lowcost carriers. Our research objective is to identify the differences between those two segments evaluating their different attributes. Besides, the paper provides the related literature review. It designs a suitable data collection and evaluation methodology for conducting the research in the Czech Republic where such studies are missing.